Preparation method and application of Ag-modified Ag / AgCl electrode

By synthesizing Ag nanoparticles on the surface of silver wire, silver foil and carbon paper and anodizing to form a dense AgCl film, the problem of insufficient sensitivity and stability of existing Ag/AgCl electrodes is solved, and chloride ions are achieved in the concrete high sensitivity measurement.

CN119433636APending Publication Date: 2025-02-14TIANJIN RES INST FOR WATER TRANSPORT ENG M O T
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411602764.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing Ag/AgCl electrodes have poor sensitivity and poor mechanical properties, and cannot effectively measure the low concentration of chloride ions in concrete.

Method used

Ag nanoparticles were synthesized on the surface of silver wire, silver foil and carbon paper by electrochemical modification, and anodized treatment was performed to increase the contact specific surface area between Ag and AgCl to form a dense AgCl film.

Benefits of technology

The sensitivity and stability of the Ag/AgCl electrode are significantly improved, and the response speed is increased by about 10 seconds on average, which can more effectively measure the chloride ions content in concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433636A_ABST
    Figure CN119433636A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an Ag modified Ag / AgCl electrode. The preparation method comprises the following steps: (1) pretreatment: respectively cleaning a silver wire, a silver foil and carbon paper; (2) electrochemical modification: synthesizing Ag nanoparticles from the pretreated silver wire, silver foil and carbon paper through electrochemical deposition; and (3) anodizing treatment: anodizing the electrochemical deposition silver wire, the silver foil and the carbon paper. The prepared Ag / AgCl electrode is more sensitive to chloride ions after being modified by nano Ag and shows excellent response performance, the response speed is averagely increased by about 10 seconds, compared with an Ag / AgCl electrode obtained by a traditional preparation method, the corresponding time can be remarkably shortened, the sensitivity is improved, the stability is more excellent, the Ag / AgCl electrode can be used in a complex structure, and the application prospect is wide. Meanwhile, the preparation method disclosed by the invention is simple, low in energy consumption and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of hydraulic structure concrete monitoring and relates to a method for preparing an Ag-modified Ag / AgCl electrode and its application. Background Art

[0002] In the traditional preparation method, the surface impurities of the silver rod or silver foil are cleaned with sandpaper, acetone, nitric acid, and alcohol, and then placed in a hydrochloric acid or NaCl solution and electrolyzed using a three-electrode system to electroplate a layer of AgCl film on the surface of the silver substrate.

[0003] The Ag / AgCl electrode prepared by this method has a short lifespan, poor mechanical properties, and cannot measure low concentrations of chloride ions in concrete. The contact surface area between Ag and AgCl is small, and the electrode sensitivity is poor; it is easily damaged when it directly contacts the concrete in the detection area; AgCl and the Ag substrate are not easily attached firmly; the film thickness on the electrode surface is uneven, and the AgCl film gradually becomes thinner and loose during use, resulting in poor electrode performance.

[0004] Therefore, it is urgent to develop an Ag / AgCl electrode with high sensitivity and excellent stability. Summary of the invention

[0005] Aiming at the defects in the existing preparation method technology that the contact surface area between Ag and AgCl is small, the electrode sensitivity is poor; the mechanical property is poor, it is in direct contact with the concrete in the detection area and is easily damaged; the adhesion between AgCl and the Ag substrate is not strong; the thickness of the film layer on the electrode surface is uneven, and the AgCl film layer gradually becomes thinner and loose during use, resulting in poor electrode performance, an Ag / AgCl electrode with high sensitivity, excellent stability and simple preparation method is provided.

[0006] In order to achieve the above-mentioned invention object, this application provides the following technical solutions: First aspect: A method for preparing an Ag-modified Ag / AgCl electrode, the preparation method comprising the following steps: (1) Pretreatment: clean the silver wire, silver foil and carbon paper separately; (2) Electrochemical modification: The pre-treated silver wire, silver foil and carbon paper are electrochemically deposited to synthesize Ag nanoparticles; (3) Anodizing: Anodizing the electrochemically deposited silver wire, silver foil and carbon paper.

[0007] Preferably, the Ag / AgCl electrode preparation method satisfies at least one of the following: In step (1), the silver wire is cleaned by ultrasonic cleaning A; In step (1), the method of ultrasonic cleaning A is to place the silver wire in a dilute nitric acid solution, an ethanol aqueous solution and deionized water in order for cleaning; In step (1), the ultrasonic cleaning time of A is 5 minutes; In step (1), the power of the ultrasonic cleaning A is 600w and the ultrasonic frequency is 40kHz; In step (1), the silver foil is cleaned by ultrasonic cleaning B; The method of ultrasonic cleaning B is to place the silver foil in the dilute nitric acid solution, the ethanol aqueous solution and deionized water in order for cleaning; In step (1), the ultrasonic cleaning time of B is 5 minutes; In step (1), the power of the ultrasonic cleaning B is 600w and the ultrasonic frequency is 40kHz; In step (1), the carbon paper is ultrasonically cleaned C; The method of ultrasonic cleaning C is to place the carbon paper in the ethanol aqueous solution and deionized water in order for cleaning; The ultrasonic cleaning time of C is 10 minutes.

[0008] Preferably, the mass fraction of the dilute nitric acid solution is 1.255%, the concentration is 0.2 mol / L, and the mass fraction of the ethanol aqueous solution is 95%.

[0009] Preferably, in step (2), the electrochemical deposition method is to use silver wire, silver foil or carbon paper as the working electrode, a 25 mm long pure silver wire as the reference electrode, and a Pt sheet as the counter electrode for electrochemical deposition. 0.1 mol / L NaNO3+3×10 -3 mol / L AgNO3 solution was used as the electrolyte.

[0010] Preferably, in step (2), the electrochemical deposition point of the silver wire is -0.3 V, and the deposition time is 30 s; The electrochemical deposition point of the silver foil is -0.3 V, and the deposition time is 30 s; The electrochemical deposition point of the carbon paper is -0.3 V, and the deposition time is 180 s.

[0011] Preferably, in step (2), the current density of the anodizing treatment is 0.4 mA / cm 2 ; The anodizing time is 30 minutes; The electrolyte used in the anodizing treatment is HCl, wherein the concentration of HCl is 0.1 mol / L.

[0012] The present application also provides an Ag-modified Ag / AgCl electrode, which is prepared by the above-mentioned Ag-modified Ag / AgCl electrode preparation method.

[0013] The present application also provides an Ag-modified Ag / AgCl electrode, which is used for preparing or as a product for use in a high-sensitivity, high-stability chloride ion selective element.

[0014] Preferably, the Ag-modified Ag / AgCl electrode is used in a chloride ion sensor to determine the chloride ion content in concrete by potential.

[0015] Second aspect: The present invention synthesizes Ag nanoparticles on the surface of silver wire, silver foil and carbon paper structure by chemical deposition method to increase their effective contact active area. Then the silver substrate is polarized to grow a dense AgCl film on its surface, so as to realize the preparation of high-sensitivity and high-stability chloride ion selective element.

[0016] The positive effects of this application are: The Ag / AgCl electrode prepared in the present application is more sensitive to chloride ions after being modified with nano-Ag, and exhibits relatively excellent response performance. The response speed is increased by about 10s on average. Compared with the Ag / AgCl electrode obtained by the traditional preparation method, it can significantly shorten the response time, improve the sensitivity, and has better stability. It can be used in complex structures, such as determining the chloride ion content in concrete. At the same time, the preparation method of the present application is simple, has low energy consumption, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0018] Figure 1 The following is a comparison of the surface microstructures of Ag / AgCl electrodes prepared by the present application and the traditional method.

[0019] Figure 2 The graph is a comparison of the response time curves of the Ag / AgCl electrodes prepared by the present application and the traditional method. DETAILED DESCRIPTION

[0020] The present application is further described below in conjunction with specific embodiments. The following are only a few embodiments of the present application, and are not intended to limit the present application in any form. Although the present application discloses the following preferred embodiments, they are not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the above disclosed technical content to make some changes or modifications are equivalent to equivalent implementation cases and are within the scope of the technical solution.

[0021] Unless otherwise specified, the raw materials in the examples of the present application were purchased from commercial sources and used directly without any special treatment.

[0022] Unless otherwise specified, the analysis methods in the examples all adopt conventional settings and conventional analysis methods of instruments or equipment.

[0023] Sources of raw materials in the following embodiments: silver - Kunshan Shangte New Materials Co., Ltd., ethanol - Tianjin Yuanli Chemical Co., Ltd., nitric acid - Tianjin Damao Chemical Reagent Factory, hydrochloric acid - Chuang'an Longbohua (Tianjin) Pharmaceutical Chemistry Co., Ltd.

[0024] Example 1 (1) Sample cleaning: Silver wire and silver foil were placed in a dilute nitric acid solution and ultrasonically cleaned for 5 min to remove surface oxides, and then ultrasonically cleaned in ethanol and deionized water for 5 min respectively; carbon paper was ultrasonically cleaned in ethanol and deionized water for 10 min respectively. (2) Preparation of sample surface nano-Ag modification Ag micro-nanoparticles were synthesized on the surfaces of silver wire, silver foil and carbon paper by electrochemical deposition to increase their effective contact active area. The deposition potential was -0.3V and the time was 30 s. The deposition potential on carbon paper was -0.3V and the time was 180 s. The material was synthesized by using a three-electrode system connected to an electrochemical workstation, using silver wire, silver foil or carbon paper as the working electrode, 25 mm long pure silver wire as the reference electrode, and Pt sheet as the counter electrode for electrochemical deposition. -3 mol / L AgNO3 solution was used as the electrolyte. The silver nanoparticles were modified and prepared on the surface of silver wire and silver foil at a deposition potential of -0.3V and a deposition time of 30 s; the silver nanoparticles were modified and prepared on the surface of carbon paper at a deposition potential of -0.3V and a deposition time of 180 s. After the modification, the electrode was rinsed with deionized water and placed in deionized water for standby use, and stored in a dark place for subsequent treatment.

[0025] (3) Anodic polarization The modified Ag electrode was subjected to polarization test on an electrochemical workstation. The modified silver wire, silver foil or carbon paper was used as the working electrode, the saturated calomel electrode was used as the reference electrode, and the Pt sheet was used as the counter electrode. The working electrode was placed in a 0.1 mol / L HCl solution for electrolysis, and the power-on time was 30 min. After polarization, the electrode was rinsed with deionized water, and then placed in a 0.1 mol / L NaCl solution for activation. During the activation process, it was stored in a dark place.

[0026] Effect Example 1 Scanning electron microscopy (SEM) was used to observe the surface morphology of Ag / AgCl electrodes prepared by traditional preparation methods and the patented method using silver wire, silver foil, and carbon paper as substrates. Figure 1 It can be seen that the surfaces of the silver wire and silver foil are clean and free of impurities after cleaning. According to the traditional method, the Ag / AgCl electrode prepared has larger AgCl particles grown on the substrate and a smaller reaction area. The Ag / AgCl electrode prepared by this patent has smaller AgCl particles, which effectively increases the effective contact active area, thereby improving the sensitivity of the electrode. At the same time, it can be seen that the Ag / AgCl electrode prepared with carbon paper as the substrate has a more compact arrangement of AgCl particles, which effectively improves the durability of the electrode. The use of nanosilver deposited on the silver wire, silver foil and carbon paper structure greatly increases the electrode reaction contact area and increases the chloride ion adsorption capacity, thereby improving the electrode sensitivity. At the same time, each nanosilver particle is attached with an AgCl film, that is, each particle can form a reversible electrode reaction with chloride ions, thereby increasing the electrode stability.

[0027] Effect Example 2 Depend on Figure 2 It can be seen that the response time of the traditional chloride ion selective element and the improved element was tested in 0.1 mol / L NaCl solution. The response time of the traditional silver wire / AgCl electrode was 30s, and the response time of the traditional silver foil / AgCl electrode was 34s. The response time of the silver wire / AgCl@Ag electrode modified with nanosilver particles was 20s, the response time of the silver foil / AgCl@Ag electrode was 25s, and the response time of the carbon paper / AgCl@Ag electrode was 23s.

[0028] After being modified with nano-Ag, the electrode is more sensitive to chloride ions and exhibits excellent response performance. The response speed is increased by about 10s on average.

[0029] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A method for preparing an Ag-modified Ag / AgCl electrode, characterized in that: The preparation method thereof comprises the following steps: (1) Pretreatment: clean the silver wire, silver foil and carbon paper separately; (2) Electrochemical modification: The pre-treated silver wire, silver foil and carbon paper are electrochemically deposited to synthesize Ag nanoparticles; (3) Anodizing: Anodizing the electrochemically deposited silver wire, silver foil and carbon paper.

2. The method for preparing the Ag-modified Ag / AgCl electrode according to claim 1, characterized in that: The Ag / AgCl electrode preparation method satisfies at least one of the following: In step (1), the silver wire is cleaned by ultrasonic cleaning A; In step (1), the method of ultrasonic cleaning A is to place the silver wire in a dilute nitric acid solution, an ethanol aqueous solution and deionized water in order for cleaning; In step (1), the ultrasonic cleaning time of A is 5 minutes; In step (1), the power of the ultrasonic cleaning A is 600w and the ultrasonic frequency is 40kHz; In step (1), the silver foil is cleaned by ultrasonic cleaning B; The method of ultrasonic cleaning B is to place the silver foil in the dilute nitric acid solution, the ethanol aqueous solution and deionized water in order for cleaning; In step (1), the ultrasonic cleaning time of B is 5 minutes; In step (1), the power of the ultrasonic cleaning B is 600w and the ultrasonic frequency is 40kHz; In step (1), the carbon paper is ultrasonically cleaned C; The method of ultrasonic cleaning C is to place the carbon paper in the ethanol aqueous solution and deionized water in order for cleaning; The ultrasonic cleaning time of C is 10 minutes.

3. The method for preparing the Ag-modified Ag / AgCl electrode according to claim 2, characterized in that: The mass fraction of the dilute nitric acid solution is 1.255% and the concentration is 0.2 mol / L, and the mass fraction of the ethanol aqueous solution is 95%.

4. The method for preparing the Ag-modified Ag / AgCl electrode according to claim 1, characterized in that: In step (2), the electrochemical deposition method is to use silver wire, silver foil or carbon paper as the working electrode, 25 mm long pure silver wire as the reference electrode, and Pt sheet as the counter electrode for electrochemical deposition. The electrolyte is 0.1 mol / L NaNO3+3×10 -3 mol / LAgNO3 solution.

5. The method for preparing the Ag-modified Ag / AgCl electrode according to claim 1, characterized in that: In step (2), the electrochemical deposition point of the silver wire is -0.3 V, and the deposition time is 30 s; The electrochemical deposition point of the silver foil is -0.3 V, and the deposition time is 30 s; The electrochemical deposition point of the carbon paper is -0.3 V, and the deposition time is 180 s.

6. The method for preparing the Ag-modified Ag / AgCl electrode according to claim 1, characterized in that: In step (3), the current density of the anodizing treatment is 0.4 mA / cm 2 ; The anodizing time is 30 minutes; The electrolyte used in the anodizing treatment is HCl, wherein the concentration of HCl is 0.1 mol / L.

7. An Ag-modified Ag / AgCl electrode, prepared according to the method for preparing an Ag-modified Ag / AgCl electrode as claimed in any one of claims 1 to 6.

8. An Ag-modified Ag / AgCl electrode as claimed in claim 7, which is used for preparing or as a product in a high-sensitivity and high-stability chloride ion selective element.

9. The use according to claim 8, characterized in that In the chloride ion sensor, the chloride ion content in concrete is determined by potential.